Benchmarking Geant4 for spallation neutron source calculations. (September 2016) - DiJulio, Douglas D.; Batkov, Konstantin; Stenander, John; Cherkashyna, Nataliia; Bentley, Phillip M.
Abstract: Geant4 is becoming increasingly used for radiation transport simulations of spallation neutron sources and related components. Historically, the code has seen little usage in this field and it is of general interest to investigate the suitability of Geant4 for such applications. For this purpose, we carried out Geant4 calculations based on simple spallation source geometries and also with the the European Spallation Source Technical Design Report target and moderator configuration. The results are compared to calculations performed with the Monte Carlo N- Particle extended code. The comparisons are carried out over the full spallation neutron source energy spectrum, from sub-eV energies up to thousands of MeV. Our preliminary results reveal that there is generally good agreement between the simulations using both codes. Additionally, we have also implemented a general weight-window generator for Geant4 based applications and present some results of the method applied to the ESS target model.